Results of State Legislative Intervention in Assistance to Household Debt: The Example of Two Greek Regions - Paraskevi KTENIDOU; Simeon KARAFOLAS (Communications of International Proceedings, 2025)
During the Greek economic crisis of the 2010s, one of the most critical social and economic issues was the inability of individuals to fulfill their loan obligations to banks. To address the problem, the Greek state took some key legislative measures under Law 3869/2010. It focused on individuals without commercial status and their inability to service the loan exposures they had undertaken. The paper examines the evolution of resources to the judicial settlement of their debts by these population groups. The examination focuses on two of the thirteen regions of Greece — Eastern Macedonia and Thrace, and Sterea Ellada — which have approximately the same population. The examination compares the evolution of macroeconomic parameters to see if the specificities of each region influenced the evolution of appeals. Initially, the legislative framework, the conditions for inclusion, the scope, and the regulatory framework are presented, along with the main amendments that occurred during the law's validity. The data collected in the context of a survey conducted by the local Justices of the Peace in the two regions are then presented, namely the number of Applications submitted under Law 3869/2010 per region during the years of the economic crisis 2011-2019. The survey methodology is presented. The data obtained from the answers conducted in the courts of the two Regions of Greece, Eastern Macedonia and Thrace, and Sterea Ellada are then presented. Here, the evolution of appeals across regions is interpreted. These results are compared with other macroeconomic factors, in particular unemployment and GDP, across the two regions. The analysis of the numbers by region makes the picture of the economic crisis clearer and more interesting, as it is more targeted to each region's specific characteristics.
Keywords: Household debt; legislation; economic crisis; Greece